Hubungan antara Dukungan Keluarga Melaui Interaksi Sosial Upaya Penyediaan Transportasi Finansial dan DUkungan dalam Menyiapkan Makanan dengan Respon Kehilangan pada Lansia di Desa Pekaja Kalibagor Kabupaten Banyumas - Wijayanti, Rahayu; Sahar, Junaiti; Sutanto, (Jurnal Keperawatan Soedirman, 2007)
This study was descriptive corelational with cross-sectional design that aims to examine the relationship between family support and the older people loss response at Pekaja village kalibagor Public Health Center. The population were 150 older people whose ≥ 60 years old and lived at Pekaja village, Kalibagor Public Health Center. The sample size were 150 older people, lived with thir family, healthy and ready to be respondent, and the number for each ranking are determined by using population total sampling. Chi-square was used to examine the relationship between family support and the older people loss response. The result of the study showed that the older people with adaptif loss responses were 80 peoples (53,3%), more than the older people with unadaptif loss respones 70 (46,7%). From correlational analysis with p=0,05 there were the significant relationship between the family support and loss respone of the older people, the were significantly correlated interaction social support (p = 0,039), transportation aids support (p = 0,019), financial support (p = 0,04) and family support for preparing of some food (p = 0,17). The kind of family support that there were more dominant relationship with loss respone were interaction social support. The study concluded that family support needed the older people to adapt changing from effect aging process, especially interaction social family support was needed